Suffragette fascists : Emmeline Pankhurst and her right-wing followers. - Webb, Simon, 1954- (Pen & Sword History, 2020)
Emmeline Pankhurst is seen today as a valiant champion of democracy, but in the 1930s certain prominent former suffragettes were comparing her to Hitler and Mussolini. It was suggested that Mrs. Pankhurst and her Women's Social and Political Union could be viewed as a proto-fascist movement; an idea likely to strike the modern reader as grotesque. Yet the WSPU certainly had much in common with the fascist parties that emerged after the end of the First World War. The group was financed by wealthy and aristocratic backers, and terrorism, in the form of bombing and arson, was widely used against working-class men and women. This, together with the rampant anti-Semitism and ambivalent attitude to democracy, all indicate that there was more to the suffragettes than we now realize. Few people today, for example, know that Emmeline Pankhurst was an advocate of ethnic cleansing and the use of concentration camps, nor that her daughter was imprisoned during the Second World War for pro-Nazi activities.